Islamic financing schemes for smes in Malaysia: a case study on the usage and effectiveness - Ahmad, Ismail; Ali, Husniyati; Pyeman, Jaafar (2011)
Small and medium enterprises (SMES) formed part of important commercial activities in Malaysia. SMEs play important roles in job creation, in providing a resilient industrial base for adapting to turbulence, and in creation of an internationally competitive industrial structure. SMEs are often small and inexperienced as compared to many larger and well established multinational companies. Banks are reluctant to lend money to SMEs due to substantial amount of risk bank to undertake. In an event of any default payment it affects the bank's lending ability in the future. Due to this, the government established Credit Guarantee Corporation (CGC) in 1972, as one of financial institutions with the mission to help SMEs that do not have any collateral or record in securing loan from financial institutions. It is proven that the establishment of CGC had contributed to the expansion of many types of businesses from the agriculture sector to manufacturing sector. Various guarantee schemes, may it be conventional or Islamic, have been offered by the organization to assist entrepreneurs to secure loan whether as a starts up capital or for business expansion. One of the earliest Islamic guarantee scheme introduced by the corporation is the Islamic Banking Guarantee Scheme (IBGS). This scheme was introduced as alternative to conventional financing, which in nature the transaction is free from interest and highly recommended by the religion. To what extend the scheme offered by CGC has been utilized by the SMEs? Does the scheme offered is similar to the conventional one? Is the scheme offered effectively and efficiently managed by the clients? A set of questionnaires were distributed to the CGC's clients to seek their opinion on the IBGS. Correspondingly, assessment is made on the financial statements of selected SMEs' firms (logistics and transportation) such as income statement and balance sheet. Base on the financial ratios analysis it gives advantage to entrepreneurs to be ahead from their competitors since the ratio analysis will furnish them with useful information of business performance, such as to forecast for growth and to avoid from bankruptcy. More importantly, the firm is able to survive for a longer period of time. The result shows that the overall financial performances, in term of profitability, liquidity, solvency and efficiency for transport and logistics firms, are excellent over the last five years.